Microalgae/cyanobacteria: the potential green future of vitamin B12 production - Durdakova, Michaela; Kolackova, Martina; Janova, Anna; Krystofova, Olga; Adam, Vojtech; Huska, Dalibor (Critical reviews in food science and nutriton, 2024)
This review summarizes the available information about potential sources of vitamin B12, especially for people who follow a vegan or vegetarian diet and inhabitants of poor countries in the developing world. Cyanobacteria and microalgae approved for food purposes can play a critical role as promising and innovative sources of this vitamin. This work involves a discussion of whether the form of vitamin B12 extracted from microalgae/cyanobacteria is biologically available to humans, specifically focusing on the genera Arthrospira and Chlorella. It describes analyses of their biomass composition, cultivation requirements, and genetic properties in B12 production. Furthermore, this review discusses the function of cobalamin in microalgae and cyanobacteria themselves and the possibility of modification and cocultivation to increase the content of B12 in their biomass.
Keywords: mikrořasy; vitamin B 12; sinice; Vitamin B 12; Chlorella; Humans; Cyanobacteria; Biomass; Microalgae; lidé; Vitamins; vitaminy; biomasa